An Analytical Design Method for Steel-Concrete Hybrid Walls. (February 2017) - Plumier, André; Dragan, Dan; Huy, Nguyen Quang; Degée, Hervé
Abstract: The design of concrete walls or columns reinforced by several encased steel profiles, also called hybrid walls, is similar to the one of classical reinforced concrete, although specific features require adequate design approaches. Experimental research and numerical models demonstrated the feasibility and validity of such structural components, but simple and practical design methods are still lacking regarding their shear resistance. The evaluation of longitudinal shear action effects at the steel profile–concrete interface is a key aspect: research results have been achieved in a more or less recent past for different types of connection but without leading to design conclusions. In this paper, the classical equivalent truss model for reinforced concrete subjected to shear is extended to take into account the contribution of the encased profiles to the shear stiffness and strength. Resulting action effects in the steel profiles, in the concrete and at the steel profile–concrete interfaces are established which allows performing design checks for those three components. In particular, it is evidenced that friction is one of the main component of the resistance to longitudinal shear at the steel profile-concrete interface. It can be directly checked since the proposed method clearly identifies the compression stresses at that location. The validity of the method is assessed by referring to tests results from experimental campaigns in China and in Europe. Some of these tests were carried out without shear connectors welded to the encased steel profiles allowing however achieving the full bending resistance of the element without any apparent problem related to longitudinal shear, like slippage between concrete and steel profile. For some other tests, failure was observed as a consequence of an insufficient shear connection. A detailed assessment of these results shows that the new design proposal is perfectly consistent with all the experimental observations.